A Stochastic Switched Epidemic Model with Two Epidemic Diseases. (25th March 2021) - El Koufi, Amine; Bennar, Abdelkrim; Yousfi, Noura
Abstract : In this paper, we study a stochastic epidemic model with double epidemics which includes white noise and telegraph noise modeled by Markovian switching. Sufficient conditions for the extinction and persistence of the diseases are established. In the end, some numerical simulations are presented to demonstrate our analytical results.